A DEA model towards efficiency estimation of biomass energy production of agro-energy districts. (26th November 2021) - Kalioropoulou, Anna; Manos, Basil; Bournaris, Thomas
In this work, the data envelopment analysis (DEA) is applied for the estimation of relative efficiency in biomass energy production and for optimal organisation of farm planning in accordance to EU goals for renewable energy sources. Specifically, a DEA model with five inputs and one output was employed at the seven prefectures of Northern Greece. The inputs used for the purpose of this study are the main factors of agricultural production, i.e., the land available, the variable costs, the available tractors, the fertilisers and the labour used. The output is the electric energy from the biomass of crop residues and it is consistent with EU objectives for renewable energy sources. The application of the DEA model revealed four prefectures as relatively inefficient and three as relatively efficient. From the empirical analysis, a reorganisation and a better allocation of inputs for the inefficient prefectures is suggested.